2013
DOI: 10.1111/obr.12109
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth and abdominal adiposity in adults: a systematic review and meta‐analysis

Abstract: SummaryWe performed a systematic literature review on the associations between birth size and abdominal adiposity in adults, while also investigating the role of the adjustment for adult body mass index (BMI). MEDLINE, Scopus, Web of Science, LILACS and SciELO databases were searched for articles published up to February 2013. Only prospective studies were included. After screening 2,570 titles, we selected 31 publications for the narrative synthesis, of which 13 were considered to be of high methodological qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 100 publications
(340 reference statements)
1
26
0
Order By: Relevance
“…Recent studies show that obesity is a leading cause of paediatric hypertension associated with type 2 diabetes mellitus (DM) and presents a risk factor to adult cardiometabolic diseases . For adequate prevention and future obesity treatment, it is necessary to determine the link of prenatal period of obesity development and associated risk factors (genetic and environmental) with post‐natal growth patterns , and physiology of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) development and its activity from birth to childhood and later in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that obesity is a leading cause of paediatric hypertension associated with type 2 diabetes mellitus (DM) and presents a risk factor to adult cardiometabolic diseases . For adequate prevention and future obesity treatment, it is necessary to determine the link of prenatal period of obesity development and associated risk factors (genetic and environmental) with post‐natal growth patterns , and physiology of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) development and its activity from birth to childhood and later in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…17 Weight and adiposity at birth are related to future total and central adiposity, insulin resistance, diabetes, cardiovascular disease, and death. [4][5][6]9 Previous studies have suggested that the trajectory of adiposity and weight gain from birth to 2 years of age is associated with increased childhood obesity and adverse cardiovascular risk factors in later life. 7,18,19 Given the implications for adulthood, infant, and childhood PI is an important measure to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Weight and adiposity at birth are key determinants of insulin resistance, diabetes, cardiovascular disease, and death. [4][5][6][7] While contributors to infant growth and adiposity are complex and multifactorial, data demonstrate significant influence of the intrauterine environment. 8,9 The ponderal index (PI kg/m 3 ) is a commonly used anthropometric measure of infant adiposity, and represents a phenotype that could be influenced by MgSO 4 .…”
mentioning
confidence: 99%
“…3,6 Some risk factors contributing to obesity are present already during fetal life and the effect is probably a combination of genetic and environmental factors. 7 Knowledge of the secular trends of BW is mainly based on research focused on recent periods when the obesity epidemic or the smoking era, or both, presumably has influenced BW. Two well-powered studies from Denmark and the USA spanning the mid-thirties to the mid-eighties show stable trends for mean BW.…”
Section: Introductionmentioning
confidence: 99%